Agronomic and nutritional responses of Carajas elephant grass fertilized with protected and non-protected urea - Alves, Francisco Gleyson da Silveira; Carneiro, Maria Socorro de Souza; Edvan, Ricardo Loiola; Cândido, Magno José Duarte; Furtado, Rafael Nogueira; Pereira, Elzânia Sales; Morais Neto, Luiz Barreto de; Mota, Rute Ribeiro Marins; Nascimento, Keuven dos Santos (Semina: Ciências Agrárias, 2018)
The objective of this study was to assess the agronomic and nutritional responses of the elephant grass cultivar Carajas when subjected to fertilization with protected and conventional urea. A randomized block design with 4Ã—2+1 factorial arrangement was adopted. The treatments consisted of four doses (100, 200, 400, and 800 kg N ha-1), two nitrogen sources (conventional and protected urea), and one additional treatment without fertilization. The experiment was carried out from October 2015 to March 2016, in a semi-arid region with a dystrophic yellow latosol type soil. The application of conventional urea was done with each of the multiple cuts performed per year, whereas the protected urea was applied in a single dose. Total senescence rate (TSR), leaf and stem elongation, height, tiller density, total forage biomass, green leaf and stem biomass, and dry matter all increased with increasing N doses. However, the phyllochron, live material/dead material ratio, and agronomic efficiency all decreased with N increasing dose. Plants fertilized with protected urea presented greater TSR and phyllochron. Mineral matter content was higher in plants fertilized with conventional urea. Neutral detergent fiber content was maximized at a dose of 437.63 kg N ha-1. The protected urea resulted in a higher value of leaf/stem ratio at the 400 kg N ha-1 dose, whereas ether extract and crude protein at the 800 kg N ha-1. With application of conventional urea, the highest crude protein value occurred at a dose of 100 kg N ha-1. The morphogenesis, structure, production, and chemical composition of elephant grass 'Carajas' were all positively influenced when nitrogen doses were increased, with the recommended optimal dose for use being 400 kg N ha-1 for both sources. The use of protected urea is recommended because of its slow release and need for only a single application.